The improvement of the company's environmental performance through the application of Green Lean/Lean and Green approach - Malgorzata Szymanska-Bralkowska; Ewa Malinowska (Institute of Economic Research (IER), 2017)
Green Lean (Lean and Green) approach is based on the lean method. As the literature and case studies show the Japanese quality improvement tools can be used in environmental management as well as in quality management. Companies that focus on sustainability may use those tools and methods to improve its processes and eliminate green waste at the same time. The research concentrates on the examples of the companies that started to implement the Green Lean (Lean and Green). The purpose of the article is to present how the application of Green Lean (Lean and Green) approach improves the environmental performance of the company and what are the benefits. Critical review of the literature, observation, interviews in selected researched companies. By identifying and eliminating the green waste i.a. in energy, materials, garbage, water, emissions, biodiversity, transportation researched companies are minimizing its negative impact on environment. As the research shows the employees should be motivated and involved in the process so does the management to make it work. Green Lean (Lean and Green) approach enables the companies to perform in profitable and sustainable way at the same time.
Keywords: Q5; Q59; 330; Lean Management; Green Lean; Lean and Green; environment